Evaluation Policies and Educational Management: articulations, interfaces and tensions - Suzana dos Santos Gomes; Savana Diniz Gomes de Melo (Universidade Federal do Rio Grande do Sul, 2018)
ABSTRACT: This article shows notes on evaluation and management in Basic Education and Higher Education, identifying articulations, interfaces, repercussions and tensions. The results indicate that the public policies for the field since 1990 have a shared characteristic: they are based on commercial conceptions and purposes; are connected to all levels of education; and its effects have brought tensions and criticism. These require further study. Attention is drawn to the threat of privatization of federal universities, which endangers the quality of education, the situation of teachers, and the essence and purpose of these universities, subverting the concept of democratic management.